The rebirth of Keynes during the COVID-19 pandemics: A theoretical approach - Ardit Namani (CES Working Papers, 2021)
The global COVID-19 pandemic caused a severe blow to the world economy, bringing the biggest economic downturn since the Great Depression. This economic downturn was accompanied by various controversies regarding the role of the state in the economy. To withstand these shocks, most of the states started to use fiscal stimulus measures. The main purpose of this paper is to present the effects that COVID-19 caused on the world economy, as well as to review Keynes's ideas regarding the need for state intervention in the economy. The results of the study show that many countries have used monetary and fiscal stimulus measures to cope with the negative effects caused by the COVID- 19 pandemic. Thus, Keynes's ideas for state intervention in the economy are still relevant and necessary in today's economy, until the number of people infected with COVID-19 decreases and the economy reopens completely as it was before.
Keywords: 330; fiscal policy; monetary policy; COVID-19; state intervention; economy